ANALISIS MOTIVASI DALAM MENINGKATKAN PRESTASI KERJA PEGAWAI NEGERI SIPIL PADA KESATUAN PENGELOLAAN HUTAN LINDUNG LARIANG PADA DINAS KEHUTANAN KABUPATEN MAMUJU UTARA - Kamiluddin, Andi (Katalogis, 2015)
From the results of observation on the research object, namely Employees of KPH Lariang at Department of Forestry of North Mamuju, there is a phenomenon that shows low motivation of employees which its indication has an impact on the implementation of their optimal duties and functions which are not optimal, therefore the purpose of this research is to analyze the motivation in improving performance of civil servant of Lariang Protected Forest Management Unit at Department of Forestry of North Mamuju. This study is a qualitative research with five informants who were determined by using purposive technique. Callecting and gathering data were done by applying triangulation technique using observation, interviews, and documentation instruments. The result shows that the motivation of civil servant of Lariang Protected Forest Management Unit at Department of Forestry of North Mamuju in carrying out the duties and functions is still not executed well based on the analysis using Abraham Maslow's Hierarchy Theory, which includes: Physiological Needs consisting of a number of inadequate salaries, procurement of uniforms that inadequate and the provision of holiday allowance which is not sufficient; Safety and Security Needs work consisting of facilities and infrastructure which are inadequate and not conducive to use; The award needs consisting of the absence of awards given for outstanding employees, and training and career opportunities for employee are still insufficient; Self-actualization needs consisting of the opportunity to participate in education and training have not been met. While the Social Needs consisting of the relationship between leader and the employees and the relationship among the employees have been intertwined harmoniously, thus this indicator gives the smallest impact on the motivation level of KPH Lariang’s employees because theoretically this requirement has been met.